Mucin-Type O-Glycosylation in the Drosophila Nervous System - Itoh, Kazuyoshi; Nishihara, Shoko (Frontiers in Neuroanatomy, 2021)
Mucin-type O-glycosylation, a predominant type of O-glycosylation, is an evolutionarily conserved posttranslational modification in animals. Mucin-type O-glycans are often found on mucins in the mucous membranes of the digestive tract. These glycan structures are also expressed in other cell types, such as blood cells and nephrocytes, and have crucial physiological functions. Altered expression of mucin-type O-glycans is known to be associated with several human disorders, including Tn syndrome and cancer; however, the physiological roles of mucin-type O-glycans in the mammalian brain remains largely unknown. The functions of mucin-type O-glycans have been studied in the fruit fly, Drosophila melanogaster. The basic structures of mucin-type O-glycans, including Tn antigen (GalNAcα1-Ser/Thr) and T antigen (Galβ1–3GalNAcα1-Ser/Thr), as well as the glycosyltransferases that synthesize them, are conserved between Drosophila and mammals. These mucin-type O-glycans are expressed in the Drosophila nervous system, including the central nervous system (CNS) and neuromuscular junctions (NMJs). In primary cultured neurons of Drosophila, mucin-type O-glycans show a characteristic localization pattern in axons. Phenotypic analyses using mutants of glycosyltransferase genes have revealed that mucin-type O-glycans are required for CNS development, NMJ morphogenesis, and synaptic functions of NMJs in Drosophila. In this review, we describe the roles of mucin-type O-glycans in the Drosophila nervous system. These findings will provide insight into the functions of mucin-type O-glycans in the mammalian brain.